Proposed conceptual framework on cohesive effect of extrinsic and intrinsic factors on sustainable behaviours - Wai, Yoong Siew; Bojei, Jamil (Elsevier, 2015)
A great deal of evident environmental awareness, concerns and consciousness are pre-cursors to pro-environment behaviour adoption. However, the behaviour has not been sustained, where various symptoms, such as licensing and rebound effects, signify that pro-environmental behaviours are not sustained in different spatial and temporal dimensions. This study aims to expand the knowledge domain by examining the effect of intrinsic and extrinsic factors in sustaining the consistency of attitude-sustainable behaviours relations.